Water column raw data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO301 - Martin Engels; Stefan Ladage; Rüdiger Lutz; Mia Schumacher (PANGAEA, 2025)
Water column raw data were collected aboard RV SONNE during cruise SO301 (SCIROCCO: Seismic image of the Central Indian Ridge – Structure and development of oceanic core complexes; Project: Refraction and reflection seismic measurements) using a 12kHz Kongsberg EM 122 multibeam echosounder with 2x2 beam width. The expedition took place during 22.11.2023 – 04.01.2024 from Port Louis - Port Louis (Mauritius) in the South Indian Ocean. The main scientific aim of the cruise is a seismic image of the Central Indian Ridge near 25° S / 70° E in order to better understand structures and processes of magmatism and crustal extension. Data were recorded outside EEZs. Sound velocity profiles (SVP) were applied on the data for calibration. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by BGR (Bundesanstalt für Geowissenschaften und Rohstoffe), provision of the data is supported by the DAM Underway Project and published according to the FAIR principles.